Leadership Coaching: Enduring Lessons From Mythology - Forbes, Raymond L. (Advances in Social Sciences Research Journal, 2024)
The juxtaposition of leadership coaching and mythology together in the same sentence is probably enough in itself to set traditionalists on edge. How could a look at the myths of cultures thousands of years old possibly benefit a leadership coach working in a modern, complex, technologically-oriented society? While much of the current literature on leadership coaching takes a non-historical, rational-empirical approach to the subject, a great deal of practical, useful insight can be gained from assessing lessons derived from mythology. The content of leadership coaching typically focuses on the resolution of professional and organizational issues in the present and on the future development of the client. This paper will attempt to show that enduring lessons derived from a look at the mythology of six different ancient cultures are both relevant and useful to the Leadership Coach of today.